G321(P) Spontaneous remission of epilepsy in a case of mesial temporal sclerosis. (12th March 2018) - Manuel, R; Yates, L; Philip, S
Abstract : Background: Mesial temporal sclerosis (MTS) is commonly referred to as hippocampal sclerosis (HS), is the most common association with intractable temporal lobe epilepsy. The typical MRI features of hippocampal sclerosis, are unilateral volume loss and increased signal intensity on T2-weighted images. There is no sex or side preference and a proportion of cases are bilateral. Macroscopically the hippocampus is firm and shrunken. Microscopic findings include a characteristic pattern of neuronal loss and reactive gliosis that varies in severity from case to case. Mesial temporal sclerosis is an uncommon finding in children, but when it occurs, it is always associated with epilepsy. Mesial temporal sclerosis is the most frequent cause of drug-resistant temporal lobe epilepsy but has a satisfactory response to surgery, and is considered infrequent in children. Patient Characteristics: 13 year old girl, she was born at 41 week of gestation with an uneventful antenatal history. She was ventilated at birth and also treated for streptococcal meningitis. She developed seizures during this treatment period. She didn't require antiepileptic at discharge. No developmental concerns. She presented with focal seizures at the age of 3 years. Had further seizures, about one or two a year, up to the age of 6 years. Eye deviation to right side, abnormal mouthing movements, disoriented, confused, vacant, lip smacking lasting for 10 min followed by headache and vomiting with post ictal phase for two hours. She remained seizure free for the past 6 years. She was not commenced on any medication. Investigations: EEG at the age of 5 years shown clustered spike epileptiform discharges focal in the central, temporal and occipital area. MRI scan – MRI brain scan showed dilatation of the left temporal horn with left mesial temporal sclerosis. Conclusion: This is a case of mesial temporal sclerosis with spontaneous remission of epilepsy. It is extremely unusual for mesial temporal sclerosis to be spontaneously seizure free. Pathophysiological mechanism of epilepsy in mesial temporal sclerosis is not fully understood. Further imaging and pathological studies comparing similar cases against the usual MTS with drug resistant epilepsy might lead to find clinically useful indicators.